On the Mechanism of Multiple Lysine Methylation by the Human Mixed Lineage Leukemia Protein-1 (MLL1) Core Complex - Patel, Anamika; Dharmarajan, Venkatasubramanian; Vought, Valarie E.; Cosgrove, Michael S. (The Journal of biological chemistry, 2009)
Transcription in eukaryotic genomes depends on enzymes that regulate the degree of histone H3 lysine 4 (H3K4) methylation. The mixed lineage leukemia protein-1 (MLL1) is a member of the SET1 family of H3K4 methyltransferases and is frequently rearranged in acute leukemias. Despite sequence comparisons that predict that SET1 family enzymes should only monomethylate their substrates, mono-, di-, and trimethylation of H3K4 has been attributed to SET1 family complexes in vivo and in vitro. To better understand this paradox, we have biochemically reconstituted and characterized a five-component 200-kDa MLL1 core complex containing human MLL1, WDR5, RbBP5, Ash2L, and DPY-30. We demonstrate that the isolated MLL1 SET domain is a slow monomethyltransferase and that tyrosine 3942 of MLL1 prevents di- and trimethylation of H3K4. In contrast, a complex containing the MLL1 SET domain, WDR5, RbBP5, Ash2L, and DPY-30, displays a marked ∼600-fold increase in enzymatic activity but only to the dimethyl form of H3K4. Single turnover kinetic experiments reveal that the reaction leading to H3K4 dimethylation involves the transient accumulation of a monomethylated species, suggesting that the MLL1 core complex uses a non-processive mechanism to catalyze multiple lysine methylation. We have also discovered that the non-SET domain components of the MLL1 core complex possess a previously unrecognized methyltransferase activity that catalyzes H3K4 dimethylation within the MLL1 core complex. Our results suggest that the mechanism of multiple lysine methylation by the MLL1 core complex involves the sequential addition of two methyl groups at two distinct active sites within the complex.